Upaya Meningkatkan Hasil Belajar Ekonomi Melalui Model Pembelajaran Kooperatif Tipe Jigsaw Pada Peserta Didik Kelas XI-8 SMAN-4 Palangka Raya - Juliansyah Juliansyah; Ilham Ilham (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to improve learning outcomes and describe the learning activities of students in the process of economic learning using the Cooperative Type Jigsaw learning model. The subjects in this study amounted to 37 students of class XI-8 of SMAN-4 Palangkaraya. The method used is to use Classroom Action Research (CAR). For data collection techniques used are observation, documentation, and tests. research results: (1) Learning activities of students are more active during the economic learning process by using the Cooperative Type Jigsaw learning model; (2) There is an increase in economic learning outcomes. This is seen from the data on student learning outcomes, in the first cycle the average student learning outcomes were 70.14 and classical completeness was 64.86% and in the second cycle it increased to 83.24 and classical completeness was 86.49% . The minimum standard for completeness determined by schools for Economics is 75.